Perancangan Sistem Komunitas Seni dan Konten Digital Melalui Platform Berbasis Laman - Nizirwan Anwar; Randy Swandy; Habibullah Akbar; Ari Pambudi; Agus Satriawan; Rudi Heri Marwan (Ikatan Ahli Informatika Indonesia, 2021)
Currently, almost every human activity has been controlled by technology. No exception for every human being needs development to develop more advanced. No exception to the world of art and creative industries. Where intellectual resources can be explored indefinitely. Streaming services and applications are expanding on various platforms so that we can enjoy photos, music, games, pictures, videos anytime and anywhere. This is where the opportunity to develop and generate coffers through this service, namely creating various contents to be enjoyed by increasing the distribution media in the creative industry in order to raise the name of Indonesia in the international arena, especially in the creative industry.